THE AUTHORITY OF BORDERLAND MANAGEMENT IN INDONESIA - Abidin, Nuraini Els Jasmine; Deliarnoor, Nandang Alamsah (Advances in Social Sciences Research Journal, 2018)
Indonesia as one of the archipelago countries has the islands as the front or border area. The management of the border and small islands with the outer involvement of many stakeholders both at the center and in the region, given the fact that this area is still lagging far from other areas. In addition, it is necessary to harmonize between state governments in the management of each country’s border and its regulation. One of the important aspects related to the borderland is the issue of authority. The management of border areas and outer islands has not been as expected because there is no synergy between the government and local government and other stakeholders. Using normative juridical approach in terms to explain in detail and conduct in-depth analysis of government authority in the management of border areas in Indonesia. The borderland has border-related issues from various aspects; in addition there is disharmonization of the borderland which then there is harmonization of legislation in the framework of borderland management has also formulated some basic principles proposed to be used as a reference for the preparation of local regulations. One further effort in creating harmonization and synchronization of legislation in governance in the archipelago, namely by empowering maintained archives. In connection with the results of research on borderland management in Indonesia, a separate ministry of borders on borderland management in Indonesia should be established, and adopt other countries that manage borders, especially archipelagic forms.